A Guide to Environmental Farming Scheme : Agreements commencing : 01 July 2017 (W), 01 January 2018 (H) and 01 January 2019 (H & W).: Agreements commencing : 01 July 2017 (W), 01 January 2018 (H) and 01 January 2019 (H & W). ([2019]) - Northern Ireland., Department of Agriculture, Environment; Rural Affairs,
No abstract available